Connexin and pannexin (hemi)channels in the liver - Maes, Michaël; Decrock, Elke; Cogliati, Bruno; Oliveira, André G.; Marques, Pedro E.; Zaidan Dagli, Maria Lucia; Menezes, Gustavo B.; Mennecier, Gregory; Leybaert, Luc; Vanhaecke, Tamara; Rogiers, Vera; Vinken, Mathieu (Frontiers in Physiology, 2014)
The liver was among the first organs in which connexin proteins have been identified. Hepatocytes harbour connexin32 and connexin26, while non-parenchymal liver cells typically express connexin43. Connexins give rise to hemichannels, which dock with counterparts on adjacent cells to form gap junctions. Both hemichannels and gap junctions provide pathways for communication, via paracrine signaling or direct intercellular coupling, respectively. Over the years, hepatocellular gap junctions have been shown to regulate a number of liver-specific functions and to drive liver cell growth. In the last few years, it has become clear that connexin hemichannels are involved in liver cell death, particularly in hepatocyte apoptosis. This also holds true for hemichannels composed of pannexin1, a connexin-like protein recently identified in the liver. Moreover, pannexin1 hemichannels are key players in the regulation of hepatic inflammatory processes. The current paper provides a concise overview of the features of connexins, pannexins and their channels in the liver.